Determinação da concentração de nitrogênio para melhoria da degradabilidade de forragem para caprinos. - Santana Neto, José Adelson (2017)
The objective was to evaluate the dynamics of neutral detergent fiber (NDF) degradation from forage as a function of nitrogen supplementation in goats. In vitro tests were performed at the Laboratory of the Forage Sector of the Department of Animal Science belonging to the Federal University of Paraíba (UFPB), Center of Agrarian Sciences, in the city of Areia/PB. In the first experiment six concentrations of ammoniacal nitrogen (0, 5, 10, 15, 20 and 30 mg/dL) were used in culture medium of ruminal microorganisms containing buffel grass hay with substrate. For this, a completely randomized design was used, in a 6 x 9 factorial scheme, with three replications. In the second experiment, five combinations of non-protein nitrogen (urea) and true protein (casein) were used in culture medium of ruminal microorganisms containing buffel grass hay as substrate. Combinations were determined from the results of the first experiment. A completely randomized design was used in a 5 x 9 factorial scheme with three replications. In the third experiment, six different combinations of non-protein nitrogen (urea), true protein (casein) and non-fibrous carbohydrate (starch) were used in culture medium of ruminal microorganisms containing buffel grass hay as substrate. Combinations were determined from the results of the first experiment. The design was completely randomized, in the factorial scheme 6 x 9, with three replications. In all experiments the parameters evaluated were pH, ammonia concentration, microbial protein concentration, volatile fatty acid concentration and in vitro digestibility of NDF in 96 hours of incubation. In all experiments, the residues from the incubation were evaluated in relation to the NDF content and analyzed by means of a nonlinear logistic model. In the first assay, a quadratic effect (P<0.05) was observed for the ruminal concentrations of acetate and propionate, with an increase in the N-NH3 level. Treatment with 15 mg/dL of ammoniacal nitrogen in the ruminal fluid presented mean values of 57.6 and 23.1 mM for acetate and propionate, respectively, with a maximum point of 16.4 and 15 mg/dL of ammoniacal nitrogen in the ruminal liquid. The addition of urea increased the degradation rate of NDFpd from 2.5 to 20.1% compared to the treatment without addition of urea and a reduction in the discrete latency estimate of 0.34 to 2.31 hours. Urea supplementation increased the specific growth rate of microorganisms by 2.6 to 20.1%. The degradation of the NDF at the end of the incubation test showed a quadratic effect with maximum point with 17.76 mg/dL ruminal liquid. In the second assay, the substitution of urea by casein by up to 50% increased the rate of degradation of potentially degradable NDF (NDFpd) by 17.42% compared to treatment without substitution. The rate of degradation of the NDFpd decreased in treatments with 75 and 100% substitution in 6.53 and 13.57%, respectively. The 50% replacement treatment obtained a reduction in the discrete latency estimate of 1.31 hours compared to the 0% replacement treatment and a 2.7 hour reduction compared to the 100% replacement treatment. Replacement by up to 50% of non-protein nitrogen by true protein provided a microbial growth of around 16.1% more efficiently. Replacement of urea by casein did not affect (P>0.05) acetate and propionate concentrations. In the third trial, treatment with 0% PV had a higher value of microbial protein, 545.8 mg/L, while treatment with 100% PV had the lowest value among all replacement levels, 426.6 mg/L of ruminal fluid, value close to the treatment without addition of nitrogen compounds, 423.1 mg/L. Replacement of NPN by TP affected (P<0.05) the concentrations of acetate. The highest concentration of total VFAs was observed in the treatment with 100% NPN. The substitution of NPN by TP in 100% caused a decrease of 28.98% in the rate of degradation compared to the treatment without 0% of NPN. Addition of TP in substitution to 100% NPN decreased the specific growth rate of microorganisms by 29.02% and microbial growth efficiency over NDF in the 100% TP treatment by 8.86%. The use of nitrogen compounds, in general, optimized the degradation of NDF of buffelgrass. In the first test, the optimum level of ammoniacal nitrogen is 17.76 mg / dL for maximum degradation of NDF. In the second assay, the proportion of 50% NPN and 50% TP optimized the NDF degradation of buffel grass. In the third trial, the use of 100% NPN as the only source of nitrogen compound, associated with a source of NFC, in the ruminal environment, increased the concentrations of acetate and total concentration of VFA, improving the use of NDF of buffelgrass.